Service empathy. Issue 2 (11th May 2015) - Fox, Robert
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This column aims to advocate for taking an empathetic approach in the evaluation of patron-oriented digital services. Design/methodology/approach – This is a regular column with citations that the reader can use to investigate further. Findings – The column explores justification for this approach and how it fits into the larger evaluative picture. It then explores methods and tools that can be used to understand patron needs from a desirability-based approach. Originality/value – Design of effective online library services is becoming more nuanced by the need to understand patron needs from an insider's perspective. Taking a more empathetic approach will greatly complement the standard objective metrics that libraries typically engage in when performing assessment on their services.